Potentiometric Behaviour of p-Nitroaniline and its Quantification in Environmental Samples - M.H. Rizk, Nashwa (Asian Journal of Chemistry, 2011)
The construction and electrochemical response characteristics of poly(vinyl chloride) membrane sensors for the determination of p-nitroaniline were described. The sensors are based on using of ethamsylate as an ionophore and o-nitrophenyl octyl ether as plasticizer in the poly(vinyl chloride) matrix. Conventional and graphite membrane sensors were prepared and the performance characteristics are evaluated according to IUPAC recommendations, reveal fast, stable and linear response for p-nitroaniline over the concentration range 1 × 10-5-1 × 10-3 and 5 × 10-5-1 × 10-3 M with cationic slopes of 51.5 and 50.6 mV per concentration decade at pH 5 for conventional and graphite membrane sensors, respectively. Sodium tetraphenylborate was used as ionic additive with ethamsylate. The potentiometric selectivity data revealed no interference from common cations. The direct potentiometric determination of p-nitroaniline using the proposed sensors gave average recoveries of 99.7 ± 1.1 and 101.4 ± 0.9 for the conventional and graphite sensors, respectively. The sensors are used for direct measurement of p-nitroaniline content in industrial waste water. The developed method was found to be simple, accurate and precise when compared with a published spectrophotometric method.